Two manuals of reindeer diseases - Sven Skjenneberg (Rangifer, 1981)
R. A. Dieterich, J. K. Morton, & S. L. Raich. "Reindeer Health Aide Manual". Institute of Arctic Biology and Cooperative Extension Service, University of Alaska. 157pp. R. A. Dieterich (ed.). Alaska Wildlife Diseases.Compendium.University of Alaska. 524pp.